A NEW RECORD FOR THE FLORA OF IRAQ: LOTUS GARCINII DC. (PAPILIONACEAE) - Mousa, M. O. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2019)
Lotus garcinii is a new additional plant species to papilionaceae family in flora of Iraq for the first time found at Al-Imsad Dam region (South of Rutba) of Western Desert District (DWD) from Iraq. The species was collected in spring season of 2017 and 2018, preserved in National Herbarium of Iraq(BAG) with the numbers 59780, 59781 and 59782. The identification of the species was confirmed by using some Flora of the neighboring countries for Iraq, taxonomic treatment was done, and some distinguishing characters are given.